Three-dimensional structure of single-shelled bluetongue virus. - Prasad, B V (1992)
The three-dimensional structure of single-shelled bluetongue virus has been determined to a resolution of 3 nm by using electron cryomicroscopy and image-processing techniques. The single-shelled virion has a diameter of 69 nm. The three-dimensional structure of the virion has icosahedral symmetry with a triangulation number of 13 in a left-handed configuration. The three-dimensional structure can be described in terms of two concentric layers of density surrounding a central core density. Two distinctive features of the outer layer are the 260 knobby capsomeres located at all the local and strict threefold axes and the aqueous channels located at all the five- and six-coordinated positions. These protrusions extend outward from an inner radius of 28 nm. They are interconnected out to a radius of 30 nm by saddle-shaped densities across the local and strict twofold axes. The aqueous channels surrounded by these capsomeres are about 8 nm wide at the outer surface and 8 nm deep. Some of these channels extend inward, penetrating the inner layer. These channels may provide pathways for transporting the metabolites and mRNA during the transcriptase activity of the particles. The inner layer is a featureless smooth bed of density except for the indentations in register with the channels of the outer layer. We propose that the 260 capsomeres in the outer layer are made up of trimers of the major protein, VP7, and that the inner layer is composed of the second major protein, VP3. The density in the central portion of the structure at a radius of less than 21 nm is likely due to the minor proteins and the genomic RNA.